Utilizing Waste Materials in Educational Media to Foster Creativity and Language-Numeracy Skills in Young Children - Mar’atus Sholihah; Dedy Kuswandi; Pramono (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
This study aims to explore the utilization of recycled banana stem waste as educational media to enhance early literacy skills and environmental awareness among preschoolers. Rooted in the need for sustainable, low-cost, and engaging learning resources, the research addresses the growing challenge of waste management while supporting the educational development of young children. Conducted at RA An-Nur Madiun using a qualitative case study approach, data were gathered through interviews, observations, and documentation analysis. The findings reveal that using banana stem materials significantly improved children’s early literacy through multisensory and contextual learning activities, including letter recognition, phonemic awareness, and vocabulary development. Additionally, children involved in this program demonstrated heightened environmental consciousness and understanding of recycling and sustainability concepts from an early age. The study also confirms the cost-effectiveness and durability of banana stem-based media, providing an eco-friendly alternative to expensive commercial teaching aids. This research contributes to early childhood education by offering a practical model for integrating literacy development, environmental education, and sustainable practices through local resource utilization, aligning with global green and contextual pedagogy trends.